The difficult rheumatology diagnosis - Devaraj, Navin Kumar (Jimma University, 2018)
Background Rheumatoid arthritis is a devastating condition. More so, the diagnosis of seronegative rheumatoid arthritis is often fraught off with much uncertainty and that leads to further suffering to the unfortunate patient. Case Details This is a case of Madam A, who presented with many non-specific symptoms and signs involving many systems which was finally diagnosed as seronegative rheumatoid arthritis. This case explores the challenges in reaching this uncommon diagnosis and how anti-inflammatory drugs can bring a miraculous relief to the patient's suffering. Conclusion The diagnosis of seronegative rheumatoid arthritis often presents a real challenge to the medical practitioner and often requires multiple visits and/or shared multidisciplinary care for confirmation of the diagnosis. Once diagnosed and treated with disease modifying anti- rheumatic drugs, often there is a miraculous relief to the patient's suffering.